(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Ankle fractures are detected in working-age individuals in 60-70% of cases. The aim of the study was to analyze the results of surgical treatment of victims with ankle injuries of varying severity. Analysis of the treatment results for patients with intra-articular fractures of the ankle joint showed that treatment outcomes depend on the type and nature of injury, the quality of bone fragment reposition with restoration of congruence in the ankle joint. Satisfactory and unsatisfactory results were obtained in case of bimalleolar intra-articular fractures with destruction of articular surfaces of the ankle joint. Complex of rehabilitation treatments in outpatient conditions increase the efficiency of rehabilitation measures, provide early restoration of joint function and improve favorable treatment results.